THE INFLUENCE OF GROWTH OF MICRO SMALL AND MEDIUM ENTERPRISES (UMKM) AND UNEMPLOYMENT ON GROWTH INDONESIAN ECONOMY - Reza Juanda; Mity Risky; Rico Nur Ilham (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the influence of MSMEs (Micro, Small and Medium Enterprises), and unemployment on economic growth in Indonesia. In this study it was taken only 15 years. This research uses quantitative research methods. This research model uses multiple linear regression. The results of the study Partially the growth of Micro, Small and Medium Enterprises (MSMEs) has a negative and significant effect on Indonesia's Economic Growth. While unemployment has a negative and significant effect on Indonesia's growth. Simultaneously the Growth of Micro, Small and Medium Enterprises (MSMEs) and Unemployment have a positive and significant effect on Indonesia's Economic Growth. The magnitude of the influence of the variables Micro, Small or Medium Enterprises (MSMEs) and unemployment on Indonesia's Economic Growth is 60, 92%. While the rest is influenced by other variables outside the model of 39.08%.